Integrating Faith and Consumer Ethics: A Study of Islamic Economics Students’ Consumption Behavior - Royhan Maliki Rizqi (Yayasan Al Ma'arif Dawuhan, 2026)
Consumption behavior is an essential aspect of daily human life and a key focus within microeconomic analysis. In Islamic economics, consumption is not merely about fulfilling desires but is guided by a hierarchy of needs: dharuriyat (essentials), hajiyat (complementary needs), and tahsiniyat (luxuries). Unlike conventional economic perspectives, Islam integrates faith and consumption, emphasizing that belief (iman) plays a significant role in shaping individual behavior and worldview. This research, conducted by Royhan Maliki Rizqi, is titled